Effects of reduced follicle-stimulating hormone dosage before human chorionic gonadotropin trigger on in vitro fertilization outcomes - Zhanhui Ou; Jing Du; Nengqing Liu; Jieliang Li; Xiufeng Lin (BMC Pregnancy and Childbirth, 2023)
Abstract Objective To determine whether a reduced dose of follicle-stimulating hormone (FSH) before human chorionic gonadotropin (hCG) trigger during ovarian stimulation can affect in vitro fertilization (IVF) outcomes. Methods This study included 347 patients with a normal ovarian response who received a reduced dose of FSH before hCG trigger for 2–3 days (Group A) and 671 patients who did not receive a reduced dose (Group B) from a university-affiliated IVF center between January 2021 and December 2022. The primary endpoint was estrogen (E2) and progesterone (P) levels on the day of hCG trigger, fresh embryo transfer cycles, laboratory outcomes, and clinical outcomes between the two groups. Results On the day of hCG trigger, Group A had significantly lower E2 and P levels than those in Group B (3454.95 ± 1708.14 pg/mL versus 3798.70 ± 1774.26 pg/mL, p = 0.003; and 1.23 ± 0.53 ng/mL versus 1.37 ± 0.59 ng/mL, p < 0.001, respectively). The proportion of patients with P levels ≥ 1.5 ng/mL was 22.48% in Group A compared to 34.58% in Group B (p < 0.001), while the proportion of patients with E2 ≥ 5000 pg/mL was 15.27% in Group A compared to 25.93% in Group B (p < 0.001). The fresh embryo-transfer cycle rate in Group A was higher than that in group B (54.47% and 32.64%, respectively; p < 0.001). Despite the reduction in FSH dosage, there were no significant differences between groups regarding the number of oocytes retrieved, total number of mature oocytes, normal fertilization rate, cleavage rate, Day 3 top-quality rate, implantation rate, pregnancy rate per cycle, and early pregnancy loss rate. Conclusion While a reduced dose of FSH prior to hCG trigger during ovarian stimulation did not significantly affect IVF outcomes, it was associated with lower E2 and P levels, resulting in fewer cycles with E2 ≥ 5000 pg/mL and P ≥ 1.5 ng/mL on the day of the hCG trigger.